RAJA ALI HAJI'S PHILANTHROPIC THOUGHT: THE ROLE OF CULTURE AND LANGUAGE IN THE FORMATION OF URBAN MALAY IDENTITY - Rizki, Muh.; Yusdani, Yusdani; Marazi, Hamidullah; Rahmawati, Rahmawati (AKADEMIKA: Jurnal Pemikiran Islam, 2024)
This article explores Raja Ali Haji's philanthropic thoughts with an emphasis on the central role of culture and language in shaping Malay identity. As a 19th century Malay intellectual, Raja Ali Haji made significant contributions to the preservation and development of Malay culture and language, as reflected in his works, such as Gurindam Dua Belas, Kitab Pengetahuan Bahasa and Bustan al-Katibbin. Through a historical and literary analysis approach, this article aims to understand the concept of Raja Ali Haji's cultural philanthropy and its impact on the formation of Malay identity. By using a historical and literary analysis approach, the aim is to understand the concept of Raja Ali Haji's cultural philanthropy and its impact on the formation of Malay identity, especially in urban communities. This research reveals that Raja Ali Haji's thoughts remain relevant in the context of preserving Malay cultural and linguistic identity in the modern era. It can be seen that the thought is implemented in Malay terms, "Adat bersendi syara', syara' bersendi Kitabullah." The Malay community prioritizes adat as the basis of the concept considered in overcoming problems and answering the challenges of preserving Malay culture and language in the contemporary era. This article provides valuable insights into how the concepts of cultural and linguistic philanthropy can be adopted to address the challenges of preserving Malay culture and language in modern times.